Tingkat Pengetahuan, Sikap dan Rasionalitas Swamedikasi pada Masa Pandemi di Kota Gorontalo - Vyani Kamba; Prisca Safriani Wicita; Insyira Fadliana Basri; Pratiwi Y Ishak (Jurnal Surya Medika (JSM), 2022)
Changes in people's lifestyles tend to pay less attention to health, and the development of diseases in the community is also unavoidable, especially during the current Covid-19 pandemic. The development of this disease encourages people to look for alternative treatments that are cost-effective and therapeutically effective. In this regard, self-medication or self-medication is an alternative that is taken by the community. Community efforts to treat themselves are known as self-medication or self-medication. This study aims to determine the knowledge, attitudes, and rationality of self-medication in the community in Gorontalo City with a descriptive cross-sectional design method. The sample in this study were people who did self-medication and met the inclusion criteria, namely aged 18-60 years and willing to be respondents as many as 80. The level of knowledge related to self-medication of the people of Gorontalo City is 43.8% in the good category, self-medication attitude in a good category is 55%, and rationality is 65%. There is a significant relationship between respondents' knowledge level and self-medication attitude, with a p-value of 0.001.